2019
DOI: 10.12659/ajcr.915947
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Labial Fistula Communicating with the Duodenal Stump After Gastrectomy

Abstract: Patient: Male, 70 Final Diagnosis: Labial fistula Symptoms: Intractable discharge Medication: — Clinical Procedure: Intraluminal drainage via a rectus abdominis musculocutaneous flap Specialty: Surgery Objective: Unusual setting of medical care Background: Anastomotic failure after gastroenterological surgery is usually treated by intraperitoneal drainage and a mature ductal fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…However, the most reasonable and effective therapeutic approach for DSF remains controversial. Many studies have shown that intra-abdominal abscesses, especially hepatorenal crypt abscesses and right paracolic sulcus abscesses, are common clinical manifestations of DSF [ [3] , [4] , [5] ]. Therefore, effective drainage of abscesses is the key to treating DSF.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most reasonable and effective therapeutic approach for DSF remains controversial. Many studies have shown that intra-abdominal abscesses, especially hepatorenal crypt abscesses and right paracolic sulcus abscesses, are common clinical manifestations of DSF [ [3] , [4] , [5] ]. Therefore, effective drainage of abscesses is the key to treating DSF.…”
Section: Introductionmentioning
confidence: 99%